MODEL PENCEGAHAN KEJAHATAN SEKSUAL DI LEMBAGA PENDIDIKAN PESANTREN - Jamaludin, Ahmad; Prayuti, Yuyut (Res Nullius Law Journal, 2022)
Islamic boarding schools must be a safe and friendly place for students and female students. Pesantren educational institutions must be perpendicular to the objectives of the establishment of the pesantren, among others, teaching the values ​​of Islamic teachings in order to improve and make society much better. However, on the other hand, there are several Islamic boarding schools that are suspected of having committed a sexual crime against their students. What is more worrying is that the sexual crime was committed by the teacher or instructor of the pesantren. There needs to be preventive efforts to respond to the number of sexual crimes in Islamic boarding schools so that these incidents do not happen again. In addition to carrying out legal protection for victims which is one form of protection, prevention efforts are also part of the concept of protecting students and female students in Islamic boarding schools. The purpose of this study was to find out how the urgency of regulating efforts to prevent sexual violence in Islamic Boarding Schools and the second to realize the sexual crime prevention model at Islamic Boarding Schools in protecting santri and female students. This research was conducted using descriptive analysis method, namely providing researched data about the condition of the object under study, namely victims and the concept of preventing sexual crimes in Islamic Boarding Schools associated with laws and regulations, and normative juridical methods. The data obtained from library research is supported by field research and then analyzed qualitatively. Based on the results of the study, it was concluded that efforts to prevent sexual violence from Islamic boarding schools could be carried out by strengthening state, government and government supervision of Islamic boarding schools, conducting legal counseling on the dangers of sexual crimes so that students and female students could act when receiving sexual crimes, making a sexual crime complaint post at the Institute. Islamic boarding school education and supervision of Islamic boarding schools by the Ministry of Religion.